What works with men? A systematic review of health promoting interventions targeting men - Reid Garth; Ludbrook Anne; Douglas Flora; Robertson Lynn M; van Teijlingen Edwin (BMC, 2008)
Abstract Background Encouraging men to make more effective use of (preventive) health services is considered one way of improving their health. The aim of this study was to appraise the available evidence of effective interventions aimed at improving men's health. Methods Systematic review of relevant studies identified through 14 electronic databases and other information resources. Results were pooled within health topic and described qualitatively. Results Of 11,749 citations screened, 338 articles were assessed and 27 met our inclusion criteria. Most studies were male sex-specific, i.e. prostate cancer screening and testicular self-examination. Other topics included alcohol, cardiovascular disease, diet and physical activity, skin cancer and smoking cessation. Twenty-three interventions were effective or partially effective and 18 studies satisfied all quality criteria. Conclusion Most of the existing evidence relates to male sex-specific health problems as opposed to general health concerns relevant to both men and women. There is little published evidence on how to improve men's uptake of services. We cannot conclude from this review that targeting men works better than providing services for all people. Large-scale studies are required to help produce evidence that is sufficiently robust to add to the small evidence base that currently exists in this field.